Can NPK fertilizers enhance seedling growth and mycorrhizal status of Tuber melanosporum-inoculated Quercus ilex seedlings? - Suz, Laura M; Martín, María P; Fischer, Christine R; Bonet, José a; Colinas, Carlos (Mycorrhiza, 2010)
Although successful cultivation of the black truffle (Tuber melanosporum) has inspired the establishment of widespread truffle orchards in agricultural lands throughout the world, there are many unknowns involved in proper management of orchards during the 6-10 years prior to truffle production, and there are conflicting results reported for fertilizer treatments. Here, we systematically evaluate the combined effects of nitrogen, phosphorous, and potassium with different doses of each element, applied to either foliage or roots, on plant growth parameters and the mycorrhizal status of outplanted 3-year-old seedlings in five experimental Quercus ilex-T. melanosporum orchards. Fertilization did not significantly improve seedling aboveground growth, but the plants treated with the fertilizer 12-7-7 applied to the roots (HNr) displayed longer field-developed roots. Only the fertilizer with the highest dose of K (10-6-28) applied to the foliage (HKf) increased the probability of fine root tip colonization by T. melanosporum in field-developed roots. However, the plants treated with the same fertilizer applied to the soil (HKr) presented the highest probability for colonization by other competing mycorrhizal soil fungi. Potassium seems to have an important role in mycorrhizal development in these soils. Apart from T. melanosporum, we found 14 ectomycorrhizal morphotypes, from which seven were identified to species level, three to genus, two to family, and two remained unidentified by their morphological characteristics and DNA analyses.
Keywords: Black truffle; DNAanalysis; ectomycorrhiza; morphotyping; nitrogen; Phosphorous; Potassium; Truffle orchard